2013
DOI: 10.1287/opre.1120.1118
|View full text |Cite
|
Sign up to set email alerts
|

Balance Optimization Subset Selection (BOSS): An Alternative Approach for Causal Inference with Observational Data

Abstract: Scientists in all disciplines attempt to identify and document causal relationships. Those not fortunate enough to be able to design and implement randomized control trials must resort to observational studies. To make causal inferences outside the experimental realm, researchers attempt to control for bias sources by postprocessing observational data. Finding the subset of data most conducive to unbiased or least biased treatment effect estimation is a challenging, complex problem. However, the rise in comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…The first step in solving such problems is to establish their computational complexity. Nikolaev et al (2013) showed that BOSS is NP-hard. This section will consider the complexity of the balanced matching problem, including special cases where certain restrictions are placed on the balancing covariates.…”
Section: Complexity Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first step in solving such problems is to establish their computational complexity. Nikolaev et al (2013) showed that BOSS is NP-hard. This section will consider the complexity of the balanced matching problem, including special cases where certain restrictions are placed on the balancing covariates.…”
Section: Complexity Resultsmentioning
confidence: 99%
“…Specifically, as the residual imbalance measured by D increased, the quality of the estimated treatment effect decreased. As demonstrated by Nikolaev et al (2013), when the imbalance score for D is zero, it is possible to construct a bound on the remaining bias in the estimate of the treatment effect when certain assumptions are made concerning the form of the response function. However, these bounds do not apply when D is nonzero.…”
Section: Results With Response Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Balance Optimization Subset Selection (BOSS) framework (Nikolaev et al 2013) is used to do the selection. BOSS is a framework that allows the selection of a small control group from a larger control pool that is similar to a treatment group, where similarity is determined by a defined balance measure.…”
Section: Finding Similar Gamesmentioning
confidence: 99%